2012
DOI: 10.1002/dac.2450
|View full text |Cite
|
Sign up to set email alerts
|

Network‐coded multiple‐source cooperation aided relaying for free‐space optical transmission

Abstract: SUMMARY A network‐coded cooperative relaying aided free‐space optical (FSO) transmission scheme is designed. The resultant multiple‐source cooperation diversity is exploited by the relay to mitigate the strong turbulence‐induced fading experienced in FSO channels. At the destination, an iterative multiple source detection algorithm is proposed in conjunction with a chip‐level soft network decoding method. Our performance evaluation results using simulation analysis demonstrate that the proposed FSO multiple so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…According to (13) and (14), the destination decodes the sources' information and obtains the estimatesx 1 ;x 2 by using ML.…”
Section: Canc-af Relay Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…According to (13) and (14), the destination decodes the sources' information and obtains the estimatesx 1 ;x 2 by using ML.…”
Section: Canc-af Relay Protocolmentioning
confidence: 99%
“…They introduced some multicast mechanisms for optimization and proved that linear network coding can achieve the maximum value of each data flow. Although network coding was developed for wireline relay networks [10,11], it can also be applied to wireless networks due to the broadcast nature of the wireless medium [12,13]. Under the assumption of bit-level synchronization, physical layer network coding (PNC), which is a novel form of network coding, was discussed in [14] and [15].…”
Section: Introductionmentioning
confidence: 99%
“…This has been extensively studied in the context of optical multicast networks [9,10]. To mitigate the strong turbulence-induced fading, a cooperative relaying aided FSO transmission network based on NC and using an iterative multiple source detection scheme in conjunction with a chip-level soft network decoding at the relay and the destination node was proposed in [11]. The simulation results demonstrated that the proposed method was capable of approaching the single user bound for transmission over the gamma-gamma turbulence channel.…”
Section: Introductionmentioning
confidence: 99%
“…LEDs also have the advantage that their light output can be modulated with high-frequency signals. Besides indoor wireless communications, VLC technology can be applied to other applications such as the VLC between a traffic light and a vehicle [16] or outdoor wireless optical communications also called free-space optical communication [17][18][19]. VLC has gained much attention as a strong candidate for future indoor wireless communication because of several advantages including its unregulated huge bandwidth (nearly 400 THz) and not causing electromagnetic interference [15].…”
Section: Introductionmentioning
confidence: 99%